Equal Effort, Unequal Outcomes: The Economic Divide in English Language Learning - Kafle, Durga (Kanakai Journal, 2024)
This descriptive phenomenological study describes the economic impact on the learning of the English language among students. It aims to trace the relationship between socioeconomic status and the acquisition of English as a second language. Four participants were interviewed, and their lived experiences were analyzed to show the correlation between their economic conditions and language learning. The study includes an introduction, contextual background, a review of related literature, and the detailed narratives of the participants. The findings have shown that there is indeed a significant impact of economic status on the ability of students to learn English effectively. The results have underlined the importance of considering socio-economic factors in educational strategies to support language learning.